Upaya Meningkatkan Hasil Belajar Siswa Tentang Perubahan Lingkungan Fisik Dengan Penerapan Pembelajaran Koorperatif Tipe Jigsaw di Kelas VII B MTsN 2 Grobogan Tahun 2018/2019 - Endang Siti Rahayu (ILUMINASI: Journal of Research in Education, 2023)
EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES CONCERNING CHANGES IN THE PHYSICAL ENVIRONMENT WITH THE IMPLEMENTATION OF JIGSAW TYPE COOPERATIVE LEARNING IN CLASS VII B MTsN 2 GROBOGAN ACADEMIC YEAR 2018/2019. The aim of this research is to determine the increase in student learning outcomes after implementing the use of Jigsaw type cooperative learning in science learning. The type of research is classroom action research with the stages of each cycle consisting of planning, action, observation and reflection.The research subjects were 32 students in class VII B MTsN 2 Grobogan Semester II 2018/2019 academic year. Data collection techniques and tools use test and non-test techniques (observation and documentation). The data validation technique uses triangulation techniques. The data analysis method in this research uses qualitative data analysis. This is based on student learning outcomes in cycle II being better than in cycle I and initial learning. In the initial learning, only 10 students got a score of 75 (completed) or 31.2%, while those who got a score of 75 were 22 students or 68.8% (not completed), in the first cycle students who got a score of 75 (completed) There were only 11 students or 34.4%, while 21 students or 65.6% (not yet completed) got a score of 75, and in the second cycle, 24 students or 75% got a score of 75 (completed), and in the second cycle there were 24 students or 75% who got a score of 75. as many as 8 students or 25% (not yet completed). Student completion in cycle II experienced a significant increase. Students are starting to actively participate in lessons followed by teacher performance which is starting to improve so that it can influence student learning outcomes.Keywords: Learning outcomes, cooperative learning, type Jigsaw, science learning.AbstrakTujuan dari penelitian ini yaitu untuk mengetahui peningkatan hasil belajar siswa setelah menerapkan penggunaan pembelajaran koorperatif tipe Jigsaw dalam pembelajaran IPA. Jenis penelitian adalah penelitian tindakan kelas dengan tahapan setiap siklus terdiri dari perencanaan, tindakan, pengamatan, dan refleksi.Subyek penelitian adalah siswa kelas VII B MTsN 2 Grobogan Semester II Tahun Pelajaran 2018/2019 sebanyak 32 orang siswa. Teknik dan alat pengumpulan data  menggunakan teknik tes dan non tes (observasi dan dokumentasi). Teknik validasi data menggunakan teknik triangulasi. Metode analisis  data  dalam  penelitian  ini  menggunakan  analisis data kualitatif. Hal tersebut berdasarkan hasil belajar siswa pada siklus II lebih baik dari pada siklus I dan pembelajaran awal. Pada pembelajaran awal siswa yang mendapat nilai  75 (tuntas) hanya sebanyak 10 siswa atau 31,2% sedangkan yang memperoleh nilai 75 sebanyak 22 siswa atau 68,8% (belum tuntas), pada siklus I siswa yang mendapat nilai  75 (tuntas) hanya sebanyak 11 siswa atau 34.4% sedangkan yang memperoleh nilai 75 sebanyak 21 siswa atau 65,6% (belum tuntas), dan pada siklus II siswa yang mendapat nilai  75 (tuntas) sebanyak 24 siswa atau 75% sedangkan yang memperoleh nilai 75 sebanyak 8 siswa atau 25% (belum tuntas). Ketuntasan siswa pada siklus II mengalami peningkatan yang signifikan. Siswa mulai aktif dalam mengikuti pelajaran dengan diikuti kinerja guru yang mulai membaik sehingga dapat mempengaruhi hasil belajar siswa.